SDN based firewall using RYU controller - Omar Sati, Salem; Mahmod Attar Bashi, Zainab Senan (IEEE, 2026)
Software-Defined Networking (SDN) has emerged as an essential solution for centralized and flexible network management. However, security remains a critical concern, particularly in dynamic firewall policy enforcement. This paper proposes an SDN-based firewall using the RYU Controller to enable real-time traffic filtering, enhancing network security while minimizing latency and jitter. A custom C#-based management tool dynamically configures firewall rules, which are rigorously evaluated across different Mininet topologies of 10, 20, and 40 hosts to assess scalability. Performance metrics focus on Round-Trip Time (RTT), analyzing both Layer 3 (IP-based) and Layer 4 (HTTP/ICMP) filtering efficiency. Experimental results show the system's effectiveness in enforcing preferable access control with negligible latency overhead, even under increased network loads. The study highlights SDN's capability to deliver scalable, adaptive security solutions and provides insights for future research in large-scale and cloud environments.